2000
DOI: 10.1073/pnas.97.10.5231
|View full text |Cite
|
Sign up to set email alerts
|

NMR and mutagenesis evidence for an I domain allosteric site that regulates lymphocyte function-associated antigen 1 ligand binding

Abstract: The leukocyte integrin, lymphocyte function-associated antigen 1 (LFA-1) (CD11a͞CD18), mediates cell adhesion and signaling in inflammatory and immune responses. To support these functions, LFA-1 must convert from a resting to an activated state that avidly binds its ligands such as intercellular adhesion molecule 1 (ICAM-1). Biochemical and x-ray studies of the Mac-1 (CD11b͞CD18) I domain suggest that integrin activation could involve a conformational change of the C-terminal ␣-helix. We report the use of NMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
161
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(172 citation statements)
references
References 49 publications
11
161
0
Order By: Relevance
“…Glu-310 in ␣ L , is indispensable for Mn 2ϩ -induced activation of ␤ 2 integrins (32,33,44). Mutation of either the metal-coordinating MIDAS residue Ser-114 in the ␤ 2 I domain or Glu-310 in the ␣ L I domain C-terminal linker totally abolished Mn 2ϩ -induced ICAM-1 binding (Fig.…”
Section: The Activating Effect Of Compound 4 Is Inhibited By Compoundmentioning
confidence: 99%
“…Glu-310 in ␣ L , is indispensable for Mn 2ϩ -induced activation of ␤ 2 integrins (32,33,44). Mutation of either the metal-coordinating MIDAS residue Ser-114 in the ␤ 2 I domain or Glu-310 in the ␣ L I domain C-terminal linker totally abolished Mn 2ϩ -induced ICAM-1 binding (Fig.…”
Section: The Activating Effect Of Compound 4 Is Inhibited By Compoundmentioning
confidence: 99%
“…Thus far, structures for the ␣L I domain have been determined only in the closed conformation (15-17); however, on binding to ICAM-1, NMR signals are altered for ␤-strand 6, the C-terminal ␣-helix 6, and the loop connecting them, as well as residues in the MIDAS (32) for ICAM-1. Although the I domain is implicated as an important site for ligand binding in those integrins that contain it, we found that the isolated wild-type ␣L I domain did not support K562 transfectant binding to immobilized ICAM-1.…”
Section: Locking the Open And Closed Conformations Of The I Domain Withmentioning
confidence: 99%
“…The structure of the ␣L I domain has been determined only in the closed conformation (18); however, there is direct evidence for conformational change (19), and we hypothesized that the ␣L I domain might exist in an open conformation similar to that seen in crystal structures for ␣M (10) and ␣2 (12) I domains. We have introduced disulfide bonds into the ␣L I domain to lock it in the open or closed conformation and examined the consequences for cell adhesion (20,21).…”
mentioning
confidence: 99%